Transport, rural - Banister, D (Elsevier, 2009)
Rural transport is dominated by the car, but substantial problems exist for those without access to a car. Service provision should be based on making the best use of all cars and exploring innovative means to promote public transport through the transformation of bus operators becoming managers of mobility services. Apart from the longer distances needed to gain access to jobs and facilities, there are strong social dimensions to rural inaccessibility, and this results in exclusion from jobs and other opportunities. The physical concepts of rural remoteness need to be balanced against those relating to income. Subsidy and enhanced service provision can be used to raise relative income levels so that mobility can be increased, and this is an alternative to relocation which might increase proximity and a reduction in travel distances. These arguments are placed within the conventional accessibility paradigm and the new mobilities paradigm. Both the quality and the quantity of travel need to be assessed, and geography is still a key determinant of both. The different challenges in developing countries are presented to illustrate the point that the same problems exist, but with much greater polarization between the rich and the poor.